تطبيق العملية الفوتوحرارية في التبخير السطحي للماء Application of photothermal process for interfacial water evaporation - بوخلفة,أسماء; صولي,خولة (University of El Oued جامعة الوادي, 2026)
تعتمد العملية الفوتوحرارية في معالجة المياه على تحويل الطاقة الضوئية إلى طاقة حرارية باستخدام مواد ماصة للضوء تسمى بالمواد الفوتوحرارية. تعمل هذه العملية على تسخين الماء وتعزيز تبخره السطحي بكفاءة عالية، يليها عادة تكثيف البخار الناتج واستعادته. يهدف هذا العمل إلى دراسة إمكانية استخدام مادة فوتوحرارية تتكون أسا ًسا من الكربون المنشط المستخلص من مخلفات النخيل. وقد تم تحسين البنية الهيكلية لطبقة الكربون المنشط )AC ) بدمجها مع بوليمر حيوي )األلجينات، AG )متشابك بأيونات الكالسيوم. أجريت تجارب مخبرية لتقييم أداء المادة الفوتوحرارية المصنعة في تبخير الماء تحت تأثير عدة عوامل تجريبية. أظهرت النتائج األولية أن وجود الظاهرة الفوتوحرارية زاد من معدل تبخر الماء بمقدار خمسة أضعاف تقريبًا تحت الضوء المحاكي، وستة أضعاف تقريبا تحت ضوء الشمس. بلغت درجة حرارة سطح المادة الفوتوحرارية حوالي C43.1° تحت ضوء الشمس، و C42.8° تحت الضوء االصطناعي. بينما في حالة التبخر الطبيعي لم تتجاوز درجة حرارة الماء C.34° فيما يتعلق بتأثير بعض العوامل التجريبية، حققت الكتلة g 0.4 من الكربون المنشط أفضل أداء، بينما لم ًّما على كفاءة التبخير. مع ذلك، ت ظهر التغيرات في تركيز كلوريد الكالسيوم )2CaCl )تأثير مه أثبتت تحاليل المجهر اإللكتروني الماسح )EDX-SEM )و طيف األشعة تحت الحمراء )FTIR )أن وجود أيونات الكالسيوم )2+Ca )ي سهم في الترابط التشابكي وتقوية بنية بوليمر -1 AG. كما أن زيادة تركيز AG إلى غاية L.g 20 ت ح ّسن أداء النموذج الفوتوحراري. من جهة أخرى، فإن زيادة تركيز ملح كلوريد الصوديوم )NaCl )في الماء ال مب ّخر له تأثير طفيف فقط على أداء العملية. ومن خالل عدة اختبارات إلعادة اإلستعمال، أظهر النموذج الفوتوحراري ًء المصنّع مقبولين. استقرا ًرا وأدا ت برز هذه النتائج فعالية المادة الفوتوحرارية ال مشتقة من المخلفات الزراعية المحلية كبديل واعد وفعّال من حيث التكلفة، ومستدام بيئيًا لتطوير أنظمة معالجة المياه القائمة على الطاقة المتجددة.The use of photothermal technology in water treatment involves converting light energy into thermal energy using light-absorbing materials named photothermal materials. This process heats the water and enhances its surface evaporation with high efficiency, followed by condensation and recovery of the generated steam. This work aims to investigate the feasibility of using a photothermal material primarily composed of activated carbon (AC) derived from palm waste. The structural integrity of the AC layer was improved by blending it with a calcium-ion-crosslinked biopolymer. Laboratory experiments were conducted to evaluate several factors affecting the material's performance during the photothermal evaporation process. Preliminary results showed that the photothermal effect increased the water evaporation rate by approximately fivefold under artificial light and sixfold under sunlight. The surface temperature of the photothermal material reached approximately 43.1°C under sunlight and 42.8°C under artificial light. In contrast, the water temperature did not exceed 34°C during natural evaporation. Regarding the influence of certain experimental parameters, the use of a 0.4 g mass of AC yielded the best performance, while variations in the concentration of calcium chloride (CaCl2), showed no significant effect on evaporation performance, but SEM-EDX and FTIR characterization proved that the presence of Ca2+ ions contributes to crosslinking and strengthening the polymer structure of AG. Increasing the AG concentration up to 20 g.L-1 improves the performance of the photothermal model. On the other hand, increasing the concentration of NaCl salt in the evaporated water has only a slight effect on the performance of the process. Through several recycling tests, photothermal material demonstrated acceptable stability and performance. These results highlight the effectiveness of photothermal material derived from local agricultural waste as a promising, cost-effective, and environmentally sustainable alternative for developing renewable energy-based water treatment systems.
ثانية ماستر كيمياء
Keywords: المخلفات النباتية، المواد الفوتوحرارية، التبخر السطحي الشمسي، التبخر السطحي للماء، المياه الراكدة.; Plant waste; Photothermal materials; Solar-driven interfacial evaporation; Interfacial water evaporation; Stagnant water.